Evaluation of crack resistance of welded joints with soft interlayers - K. A. Molokov; V. V. Novikov (Advanced Engineering Research, 2022)
Introduction. Welded joints in large-sized metal structures (e.g., in the structures of ship hulls) subject to low-cycle fatigue are considered. The characteristic appearance of soft interlayers, which are significantly plastically deformed under working loads, was noted. Deformation of the metal structure with damage, especially in the form of cracks, reduces the strength and reliability of structural elements and joints. Pre-deformation negatively affects plasticity; therefore, much depends on the residual plasticity of the cracking material. At the same time, with a decrease in residual plasticity, such an important reliability indicator as the resistance of the material to crack propagation — the fracture toughness – decreases. The paper is devoted to the development of a model that includes analytical dependences for assessing the crack resistance of metal structures and their welded joints with soft interlayers according to the crack resistance limit for all crack sizes.Materials and Methods. The theory and methods of linear mechanics of materials destruction, structural-mechanical approach are used. The calculation results were analyzed and compared to the experimental data and other analytical solutions. The numerical experiment was performed for the ferrite-perlite steel grades of 10, 50, 22K, St3sp, etc., widely used in industry, as well as for alloy steels hardened to medium and high strength of 30KhGSA, 37KhN3A, etc. Results. Analytical dependences are obtained for calculating the relative crack resistance limit according to three main known mechanical characteristics of the state of the material of the soft interlayer of the welded joint.Discussion and Conclusions. The results obtained can be used to assess the crack resistance of pre-deformed structural elements and welded joints (including those with soft interlayers) operating under a transverse load. The results of experimental data and analytical calculations are shown in dimensionless form, which enables to obtain invariant results with respect to the fracture toughness limit.